Comparative analysis of concrete behaviour under compressive creep and cyclic loading. (December 2021) - Kern, Bianca; Oneschkow, Nadja; Podhajecky, Anna-Lena; Lohaus, Ludger; Anders, Steffen; Haist, Michael
Highlights: Investigates and compares the strain development of a normal-strength concrete due to static creep and cyclic loading. Shows the influence of test frequency and minimum stress level on strain development for cyclic tests. Discusses existing modelling approaches for cyclic strains with regard to the investigations presented. Abstract: The expected deformations during service life of concrete structures are described using creep models, developed for constant loading. Thereby, the effect of cyclic loading superimposed to constant loading, ubiquitously observed in practice, is excluded. Thus, the strain development due to static creep and cyclic loading of a normal strength concrete are comparatively investigated considering the influence of the minimum stress level and the load frequency. The results show that cyclic deformations are significantly higher than creep strains despite similar mean stress levels and are considerably affected by the influences. Therefore, for modelling cyclic deformation developments these influences must be considered.